Development of an Evaluative Tool for Occupational Health Service Contractors in Mining Based on CSMS - Sipayung, Christian (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
Occupational health service contractors play a key role in ensuring occupational safety and health (OSH) in high-risk industries, especially in remote operational areas. However, the selection process for contractors at PT. ABC Indonesia relies heavily on an administrative approach and lacks a comprehensive, structured, and risk-based evaluative instrument. This can affect the quality of occupational health services and contractor independence in supporting company operations. This study aims to develop a valid, objective, and applicable evaluative instrument for assessing the feasibility of occupational health service contractors based on the Contractor Safety Management System (CSMS). The research uses a Research and Development (R&D) approach in two stages: content validation using the Content Validity Index (CVI) method, with input from six experts in OSH, contractor management, and occupational health services, and the determination of priority weights using the Analytical Hierarchy Process (AHP). The instrument was based on eight CSMS domains, operationalized into 24 indicators. The results show that all indicators had high content validity with i-CVI and S-CVI/Ave values of 1.00. AHP results indicated that the most dominant criterion in determining contractor feasibility was Leadership and Top Management Commitment, followed by planning, risk control, and emergency preparedness. The final instrument is valid, consistent, and suitable for use in contractor selection at PT. ABC Indonesia. This study aims to improve the objectivity of the contractor selection process and enhance OSH service quality and operational safety in the mining industry.